2021
DOI: 10.1556/2006.2021.00025
|View full text |Cite
|
Sign up to set email alerts
|

Determination the cut-off point for the Bergen social media addiction (BSMAS): Diagnostic contribution of the six criteria of the components model of addiction for social media disorder

Abstract: ObjectiveSocial media disorder (SMD) is an increasing problem, especially in adolescents. The lack of a consensual classification for SMD hinders the further development of the research field. The six components of Griffiths’ biopsychosocial model of addiction have been the most widely used criteria to assess and diagnosis SMD. The Bergen social media addiction scale (BSMAS) based on Griffiths’ six criteria is a widely used instrument to assess the symptoms and prevalence of SMD in populations. This study aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 36 publications
8
66
1
Order By: Relevance
“…Our findings showed that the prevalence of participants whose overall score on SMA exceeds the clinical cut-off is 4.25%. This value is similar to that obtained by Luo et al ( 2021 ), who reported that 3.25% of the participants were addicted users.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings showed that the prevalence of participants whose overall score on SMA exceeds the clinical cut-off is 4.25%. This value is similar to that obtained by Luo et al ( 2021 ), who reported that 3.25% of the participants were addicted users.…”
Section: Resultssupporting
confidence: 91%
“…First, this is the first validation study of the BSMAS conducted in an Eastern European country, more precisely in Romanian culture. Previous validation studies of adapted version of BSMAS were conducted in Western (Monacis et al, 2017 ), American (Watson et al, 2020 ), and Asian cultures (Chen et al, 2020 ; Lin et al, 2017 ; Luo et al, 2021 ). Second, this is the first study based on the modern approach of GRM analysis in the framework of IRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is based on the six dimensions proposed by Griffiths [ 89 ] (i.e., salience, mood, modification, tolerance, withdrawal conflict, relapse) and consists of six items (e.g., “How often during the last year have you tried to cut down on the use of social media without success?”) that are rated on a 5-point Likert scale ranging from 1 (very rarely) to 5 (very often). Higher scores indicate a greater risk of developing social media addiction, with the score of 24 recently indicated as the best cut-off score for a possible clinical diagnosis [ 90 ]. The present study applied the Italian version of the test, developed by Monacis et al [ 91 ].…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores in this scale indicate higher problematic use of SN. The clinical cut-off for this measure is 24 [ 22 ]. As in previous studies on the general population [ 23 ], in this research, no subject exceeded the clinical cut-off for problematic use and the internal consistency of the scale was good.…”
Section: Methodsmentioning
confidence: 99%